Investigating factors that influence internet banking services in the banking industry / Abdul Kadir Othman ... [et al.] - Othman, Abdul Kadir; Mohd Abas, Mohd Khalid; Mat, Azmi; Dzulkipli, Mohd Redhuan; Abujarad, Ismael (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
Online banking or Internet banking is a common phenomenon nowadays because of its convenience. Customers can use Internet banking to practically access all the banking services offered, including deposits, transfers, and bill payments. Almost every financial institution offers various types of internet banking, which are accessible via mobile apps. This provides convenience to their consumers. This paper aims to examine the impact of Internet banking services on customer satisfaction in the banking industry. Customer satisfaction is an important factor for maintaining a long-term relationship between a company and its customers. Customer satisfaction has been proven to increase a company's profitability. However, what contributes to satisfaction needs to be explored further since previous studies are inconclusive in their findings regarding this matter. Most studies on Internet banking studies have investigated various factors including safety and reliability, transaction efficiency, customer support, service security, ease of use, performance, and service content. But, in this study, all these variables will be combined into three types of services, service security, service reliability, and service functionality and the dependent variable is customer satisfaction. The findings of the study confirm that these three factors are important to ensure customer satisfaction in using Internet banking services.